Organizational levers supporting police officers’ psychological health in the workplace after exposure to a potentially psychologically traumatic event - Deschênes, Andrée-Ann (Advances in Social Sciences Research Journal, 2021)
One in two police officers report having experienced a potentially psychologically traumatic event (PPTE) in the course of their career that has had an impact on their professional or personal life. In addition, daily exposure to PPTEs results in major adverse effects that affect all aspects of health: psychological, emotional, and physical. However, it is not necessarily PPTEs as such that cause psychological distress at work; rather, the determining factor seems to be the organization’s response to police officers’ exposure to PPTEs. The purpose of this study is therefore to identify the organizational factors that explain psychological health at work for police officers who have experienced a PPTE in the line of duty. The results show that the quality of relationships with the superior and colleagues, the availability of support such as advice, job demand, and job decision latitude are factors that partially explain the psychological distress that police officers experience at work after a PPTE [R2 = .38, p<.05; F(1,451) = 55.99, p<.001]. Conversely, quality relationships with co-workers, job demand, and job decision latitude partially account for the workplace psychological well-being experienced by officers after a PPTE [R2=.42, p<.05; F(1,457) = 109.55, p<.001]. This study highlights the importance for police organizations to promote good relationships between police officers and, above all, to encourage managers to invest in their relational skills and counseling-type social support. The study limitations and new avenues for research are also discussed.